A novel marine bacterium Exiguobacterium marinum a-1 isolated from in situ plastisphere for degradation of additive-free polypropylene - Sun, Yueling; Zhang, Ying; Hao, Xiaohan; Zhang, Xiaohan; Ma, Yongzheng; Niu, Zhiguang (Environmental pollution (1987), 2023)
As the ecological niche most closely associated with polymers, microorganisms in the ‘plastisphere’ have great potential for plastics degradation. Microorganisms isolated from the ‘plastisphere’ could colonize and degrade commercial plastics containing different additives, but the observed weight loss and surface changes were most likely caused by releasing the additives rather than actual degradation of the plastics itself. Unlike commercial plastics that contain additives, whether marine microorganisms in the ‘plastisphere’ have adapted to additive-free plastics as a surface to colonize and potentially degrade is not yet known. Herein, a novel marine bacterium, Exiguobacterium marinum a-1, was successfully isolated from mature ‘plastisphere’ that had been deployed in situ for up to 20 months. Strain a-1 could use additive-free polypropylene (PP) films as its primary energy and carbon source. After strain a-1 was incubated with additive-free PP films for 80 days, the weight of films decreased by 9.2%. The ability of strain a-1 to rapidly form biofilms and effectively colonize the surface of additive-free PP films was confirmed by Scanning Electron Microscopy (SEM), as reflected by the increase in roughness and visible craters on the surface of additive-free PP films. Additionally, the functional groups of –CO, -C-H, and –OH were identified on the treated additive-free PP films according to Fourier Transform Infrared (FTIR). Genomic data from strain a-1 revealed a suite of key genes involved in biosurfactant synthesis, flagellar assembly, and cellular chemotaxis, contributing to its rapid biofilm formation on hydrophobic polymer surfaces. In particular, key enzymes that may be responsible for the degradation of additive-free PP films, such as glutathione peroxidase, cytochrome p450 and esterase were also recognized. This study highlights the potential of microorganisms present in the ‘plastisphere’ to metabolize plastic polymers and points to the intrinsic importance of the new strain a-1 in the mitigation of plastic pollution. [Display omitted] •An additive-free PP utilizing bacterium was isolated from ‘plastisphere’.•Additive-free PP lost 9.2% of its weight after 80-day cultivation.•Surface deterioration of PP films is evidenced by visible pits and surface roughness.•Flagellar assembly and chemotaxis genes contribute to biofilm formation on PP surface.•Glutathione peroxidase may be the key enzyme in degrading additive-free PP films.